Global Asset Management Strategies, Risks, Processes, and Technologies - Pinedo, Michael.; Walter, Ingo. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book focuses on all major aspects of the asset management industry including its regulations, strategies, processes, applied technologies and risks. It provides a serious resource for readers seeking greater depth and alternative opinions on specific industry developments, and breadth for specialists interested in the dynamics of the industry.